Instrumentation handbook for biomedical engineers - Sahin, Mesut; Fidel, Howard; Perez-Castillejos, Raquel (Boca Raton : CRC Press, 2021)
The book fills a void as a textbook with hands-on laboratory exercises designed for biomedical engineering undergraduates in their senior year or the first year of graduate studies specializing in electrical aspects of bioinstrumentation. Each laboratory exercise concentrates on measuring a biophysical or biomedical entity, such as force, blood pressure, temperature, heart rate, respiratory rate, etc., and guides students though all the way from sensor level to data acquisition and analysis on the computer. The book distinguishes itself from others by providing electrical circuits and other measurement setups that have been tested by the authors while teaching undergraduate classes at their home institute over many years. Key Features:Hands-on laboratory exercises on measurements of biophysical and biomedical variablesEach laboratory exercise is complete by itself and they can be covered in any sequence desired by the instructor during the semesterElectronic equipment and supplies required are typical for biomedical engineering departments Data collected by undergraduate students and data analysis results are provided as samplesAdditional information and references are included for preparing a report or further reading at the end of each chapter Students using this book are expected to have basic knowledge of electrical circuits and troubleshooting. Practical information on circuit components, basic laboratory equipment, and circuit troubleshooting is also provided in the first chapter of the book.
S5.6 Circuit Testing and Troubleshooting -- S5.7 Data Analysis and Reporting -- References and Materials for Further Reading -- Studio 6 Oscillometric Method for Measurement of Blood Pressure -- S6.1 Background -- S6.2 Overview of the Experiment -- S6.3 Learning Objectives -- S6.4 Notes on Safety -- S6.5 Equipment, Tools, Electronic Components and Software -- S6.6 Circuit Operation -- S6.7 Detailed Experimental Procedure -- S6.8 Circuit Testing and Troubleshooting -- S6.9 Important Topics to Include in the Lab Report -- References and Material for Further Reading
OCLC-licensed vendor bibliographic record.
Keywords: Biomedical engineering; Biological apparatus and supplies; Medical instruments and apparatus; MEDICAL / Biotechnology; TECHNOLOGY / Material Science